2016
DOI: 10.1245/s10434-016-5088-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncological and Functional Outcomes between Initial Surgical versus Non-Surgical Treatments for Hypopharyngeal Cancer

Abstract: Our data revealed similar oncological outcomes, but different functional outcomes, between initial surgical and non-surgical treatments for HPC. In resectable advanced-stage HPC, iCRT resulted in better verbal communication outcomes than SRC; however, more iCRT patients required multiple surgical interventions during clinical courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
2
33
0
1
Order By: Relevance
“…In comparison, studies of patients treated with chemoradiotherapy found 36% to 70% of patients required initial gastrostomy tube placement . A comparative study of open surgery to chemoradiotherapy found a 7.1% feeding tube dependence for open surgery and 13.1% for chemoradiotherapy . One key limitation in interpreting these results is the duration of gastrostomy tube placement.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, studies of patients treated with chemoradiotherapy found 36% to 70% of patients required initial gastrostomy tube placement . A comparative study of open surgery to chemoradiotherapy found a 7.1% feeding tube dependence for open surgery and 13.1% for chemoradiotherapy . One key limitation in interpreting these results is the duration of gastrostomy tube placement.…”
Section: Discussionmentioning
confidence: 99%
“…However, organ‐conserving CRT entails significant adverse effects as surgery, with a large number of patients remaining gastrostomy tube‐dependent and tracheotomy‐dependent. Recent studies have compared the oncologic and functional outcomes of initial surgical and nonsurgical approaches for advanced hypopharyngeal cancer; initial surgery with or without radiotherapy and CRT resulted in similar 5‐year survival as did concurrent CRT, and few patients in the initial surgery group recovered their speaking ability through voice prosthesis after laryngectomy …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared the oncologic and functional outcomes of initial surgical and nonsurgical approaches for advanced hypopharyngeal cancer; initial surgery with or without radiotherapy and CRT resulted in similar 5-year survival as did concurrent CRT, and few patients in the initial surgery group recovered their speaking ability through voice prosthesis after laryngectomy. 39,40 Although no major consensus exists on recommending induction chemotherapy for advanced oropharyngeal cancer, 20 induction chemotherapy may be combined with partial laryngectomy as a larynx preservation strategy 8,41 in patients with advanced hypopharyngeal cancer when total laryngectomy is otherwise indicated. Recent studies attempting conservative partial laryngectomy followed by appropriate postoperative adjuvant treatment 30,42 in patients with F IGUR E 2 A, B, Overall survival of patients with oropharyngeal and hypopharyngeal cancers and C, D, disease-free survival of patients with oropharyngeal and hypopharyngeal cancers stratified by clinical stage (III/IVA) and surgery status (yes/no).…”
Section: Discussionmentioning
confidence: 99%
“…Se analizó el beneficio de la quimioterapia para cada localización en la supervivencia global, observándose en el grupo de tumores de hipofaringe que la supervivencia a los 5 años era un 3,9 % mejor en aquellos pacientes que habían recibido quimioterapia concomitante. 20 Se han publicado estudios no aleatorizados, algunos específicos en cánceres de la laringe, otros de la hipofaringe [21][22][23][24] y otros mezclando cánceres de laringe e hipofaringe 25,26 . Beauvillain et al 21 compararon los resultados del tratamiento conservador frente a la cirugía radical en tumores resecables de hipofaringe; establecieron dos grupos, el primero tratado con quimioterapia de inducción seguida de cirugía radical con radioterapia postoperatoria y el segundo tratado con quimioterapia de inducción seguida de radioterapia.…”
Section: Discussionunclassified